First record of intersexuality in the Amazon River shrimp Macrobrachium amazonicum (Heller, 1862) (Caridea: Palaemonidae) - Paschoal, Lucas R. P. [UNESP]; Zara, Fernando J. [UNESP] (Oxford University Press (OUP), 2017)
Intersexuality in a gonochoric palaemonid shrimp is reported for the first time in a wild population of Macrobrachium amazonicum (Heller, 1862). This phenomenon was confirmed based on an investigation of anatomic and morphometric traits and the ultrastructure of gonopores. The intersex had both reproductive organs despite the absence of vitellogenic oocytes and spermatozoa. This individual had a vestigial male gonopore complex and female gonopores. The intersexuality was related to a genetic mutation and/or hormonal disruption because there was no detection of chemicals in the water or parasites in the samples. Non-functional hermaphroditism is a very rare event (0.06%) in M. amazonicum, indicating that this species is gonochoric, and intersex individuals are not reproductively viable.
Keywords: Gonopores; Morphology; Non-functional hermaphroditism; Ultrastructure